EFFECT OF OZONE TREATMENT ON CAULIFLOWER - S.MADUMITHA* and R.RADHA, (The Journal of Research ANGRAU, 2020)
The study focused on the effect of ozone treatment on cauliflower and to determine an optimum treatmenttime for effective disinfection without alterations in the keeping quality and sensory attributes of the treatedsample. A domestic bubbling ozone generator was used in this experiment. To assess the time required fordisinfection, four time intervals were tested with an interval of 5 minutes upto 20 minutes.Treated samples ofcauliflower were analysed for microbial tests, keeping quality and sensory evaluation. Microbial tests showeda prominent decrease in microbial population after each treatment. Also, the keeping quality of the treatedsamples under refrigeration and room temperature gave a satisfactory score for freshness. Sensory evaluationfor ozone-treated samples was conducted to examine the changes in the sensory attribute after variation.Among the different time intervals, 20 minutes of disinfection with ozone had a better score than other timeintervals in all the experiments.